Immunosuppressive Effect of Methanol Extract and Ethyl Acetate Fraction of Breadfruit [Artocarpus altilis (Park.) Fosberg] Leaves: Efek imunosupresif ekstrak metanol dan fraksi etil asetat daun sukun [Artocarpus altilis (Park.) Fosberg] - Dwi Hadi Setya Palupi; Andreanus A. Soemardji; Maria Immaculata Iwo (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: Artocarpus sp. contained a variety of flavonoids, some of which have been shown to reduce inflammation. In vitro anti-inflammatory activity of breadfruit (Artocarpus altilis (Park.) Fosberg) has been demonstrated. Chronic inflammation can occur when immune defence mechanisms are activated by inflammatory conditions. Objectives: This study examined breadfruit leaf methanol extract and ethyl acetate fraction immunosuppressive effects. Material and Methods: The bioactive compounds in breadfruit leaves were extracted in methanol via maceration and fractionation in ethyl acetate via liquid-liquid extraction. The in vivo immunosuppressive effect was evaluated in male Swiss albino mice by humoral antibody titer, delayed-type hypersensitivity, and phagocytic index assays. Results: According to phytochemical screening, flavonoids and steroids were found in the extract and its ethyl acetate fraction. The breadfruit leaf extract and fraction showed an immunosuppressive effect through phagocytic index<1, and the thymus gland index was significantly decreased (p<0.05) compared to control. The breadfruit leaf extract and the ethyl acetate fraction were able to inhibit the production of antibodies and DTH reactions, two types of immune responses. Conclusions: The extract of breadfruit leaves and the ethyl acetate fraction showed immunosuppressive properties.